Aplicação de fibrados e conexões de fibrados na física teórica - Rodrigues, Arthur Costa (Universidade Federal de São Carlos, 2025)
This work addresses the applications of fiber bundles and fiber bundle connections in theoretical physics, highlighting their relevance in the formulation of modern theories such as Gauge Theory, Dirac’s magnetic monopole, the Aharonov-Bohm effect, Yang-Mills theory, and instantons. Using concepts from differential geometry, such as fiber spaces, connections, curvature, and holonomy, we explore how these mathematical structures provide a unifying language for describing fundamental physical phenomena. Initially, we introduce fiber bundles as a generalization of Cartesian products, emphasizing their role in defining physical fields in curved spaces or those with nontrivial topologies. Connections are described as tools for transporting information along the bundle, establishing the parallel between covariant derivatives and local transformations in physical theories. Examples of tangent bundles and principal bundles are discussed as fundamental cases for applications in Physics. In Gauge Theory, fiber bundles provide the necessary formalism to describe fundamental interactions, such as electromagnetic, weak, and strong forces, using local symmetry groups. We explore Dirac’s magnetic monopole as a singular solution to Maxwell’s equations, whose existence is intrinsically linked to the topology of fiber bundles. The Aharonov-Bohm effect, in turn, demonstrates how connections can mediate physical effects in regions where local fields vanish, revealing the importance of the global properties of spacetime. We then move to Yang-Mills theory, which generalizes electromagnetism to non-Abelian symmetry groups, forming the foundation of the Standard Model of Particle Physics. In this theory, the curvatures of fiber bundles correspond to the forces associated with Gauge fields. We also discuss instantons, classical solutions of the Yang-Mills equations, which play a significant role in the description of quantum transitions and phenomena such as spontaneous symmetry breaking. Throughout this study, we emphasize how fiber bundles encapsulate information about the geometric structure of spacetime and enable an accurate description of phenomena involving topology, symmetry, and local interactions. This geometric formalism not only clarifies the relationship between mathematics and physics but also opens possibilities for developing more comprehensive and unifying theories in the future.
Aplications of fiber bundles and fiber bundle connections in theoretical physics
Keywords: Geometria diferencial; Fisica; DIfferential geometry; Physics; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA::GEOMETRIA DIFERENCIAL; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DAS PARTICULAS ELEMENTARES E CAMPOS::TEORIA GERAL DE PARTICULAS E CAMPOS